2005
DOI: 10.1002/ajh.20394
|View full text |Cite
|
Sign up to set email alerts
|

hTERT mRNA levels by real-time RT-PCR in acute myelogenous leukemia

Abstract: The purpose of this study was to investigate whether levels of hTERT mRNA, as determined by real-time RT-PCR, are associated with prognosis and clinical course in AML patients. Fifty-four bone marrow specimens from 21 patients diagnosed with de-novo AML were included. The level of hTERT mRNA was measured with the Telo TAGGG hTERT Quantification Kit (Roche Diagnostics, Mannheim, Germany), using a LightCycler Instrument (Roche Diagnostics). The level of hTERT mRNA was determined as the relative ratio (RR), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…In this study, the highest value of hTERT mRNA was obtained in pre-B cell ALL and no correlation was also found between the blast percentages and the hTERT mRNA values. Similar results have been reported by Huh et al in AML patients and they suggested that hTERT value may be associated with the telomerase activity of blasts, not with the blast counts [6]. Our results may support this suggestion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the highest value of hTERT mRNA was obtained in pre-B cell ALL and no correlation was also found between the blast percentages and the hTERT mRNA values. Similar results have been reported by Huh et al in AML patients and they suggested that hTERT value may be associated with the telomerase activity of blasts, not with the blast counts [6]. Our results may support this suggestion.…”
Section: Discussionsupporting
confidence: 91%
“…No significant difference was also found between the subgroups of those parameters except hemoglobin level. In the literature, there are a number of studies which found both significant and not significant correlation between the WBC count and TA [6,8,17,21]. In this study, the highest value of hTERT mRNA was obtained in pre-B cell ALL and no correlation was also found between the blast percentages and the hTERT mRNA values.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…They hold the promise of being effective agents for the treatment of solid tumors [9,23,24]. A few investigations showed that the existence of hypoxic areas in tumor tissues and the expression of telomerase in cancer cells can be employed to achieve cancer targeting treatment [25][26][27][28][29][30][31]. Accordingly, the modifications to regulate SG600 with two promoters could restrict adenoviral replication to tumors and thus achieve better tumor-selective oncolysis.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 Telomerase activity and hTERT expression level in AML has been investigated in different works. [6][7][8] Recently, Huh et al 9 demonstrated by real-time RT-PCR that hTERT expression was higher in patients with AML at diagnosis and during relapse than during remission and that patients who failed to achieve complete remission had a high level of hTERT mRNA, this suggesting that hTERT mRNA may be a useful marker for prognosis prediction and disease monitoring in AML patients. Pharmacological telomere inhibition can sensitise drug-resistant and drug-sensitive cells to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%